PENERAPAN METODE PEMBELAJARAN AKTIF COOPERATIVE SCRIPT UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN STRUKTUR ATOM DI KELAS X MIA SMA NEGERI 1 KEPENUHAN KABUPATEN ROKAN HULU - Handasari, Dessi Handasari; M Noer, Asmadi M Noer (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Research on the application of active learning Cooperative Script method has been done in class X of SMAN Kepenuhan Kabupaten Rokan Hulu on the subject of atomic structure. Based on the results of observations conducted by researchers at the SMAN1Kepenuhan Kabupaten Rokan Hulu do known that learning is teacher centered, so that students become less active and negatively affect student achievement. The objective was to determine the increase in student achievement and increase student achievement category. The research form is an experimental research with pretest-posttest design. The sample consisted of two classes, namely class X MIA1 as the experimental group and the class X MIA2 as the control group. The experimental group is the group of students who were treated by applying the active learning of Cooperative Script method, while the control group was treated with information discussion methods. Data analysis technique used is the t-test. The results showed tarithmetic>ttable (2,07 > 1,68) and N-gain of the experimental group is 0,754 which includes the high category. Therefore, it can be concluded that the application for active learning Cooperative Script method can increase student achievement in the subject of anatomic structure in SMAN 1 Kepenuhan Kabupaten Rokan Hulu. Keywords : Cooperative Script, Learning Achievement, Atomic Structure